2016
DOI: 10.4240/wjgs.v8.i10.706
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of docetaxel, cisplatin and capecitabine as preoperative chemotherapy in resectable gastric cancer

Abstract: AIMTo investigate the feasibility of preoperative docetaxel, cisplatin and capecitabine (DCC) in patients with resectable gastric cancer.METHODSPatients with resectable gastric cancer fulfilling the inclusion criteria, were treated with 4 cycles of docetaxel (60 mg/m2), cisplatin (60 mg/m2) and capecitabine (1.875 mg/m2 orally on day 1-14, two daily doses) repeated every three weeks, followed by surgery. Primary end point was the feasibility and toxicity/safety profile of DCC, secondary endpoints were patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Docetaxel belonging to the taxane family is a promising anticancer agent which is a semi-synthetic derivative from the needles of European yew (Taxus baccata) (16). Docetaxel has been widely used to treat breast (17), prostate (18), bladder (19), gastric (20), ovarian (21), head and neck (22) and non-small cell lung (23) cancers. Furthermore, the role of docetaxel in HCC treatment has been recognized due to its low toxicity and high therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Docetaxel belonging to the taxane family is a promising anticancer agent which is a semi-synthetic derivative from the needles of European yew (Taxus baccata) (16). Docetaxel has been widely used to treat breast (17), prostate (18), bladder (19), gastric (20), ovarian (21), head and neck (22) and non-small cell lung (23) cancers. Furthermore, the role of docetaxel in HCC treatment has been recognized due to its low toxicity and high therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a trial reports that BEV plus DCC as neoadjuvant regimen presents pleasing treatment response in previous patients with unresectable LAGC or paraaortic lymph node metastatic gastric cancer, and the data shows that the ORR is 64.3%; meanwhile, the pathological complete regression rate is 12.9% ( 22 ), which indicates that neoadjuvant BEV plus DCC may improve treatment response in patients with gastric cancer. Thus, our study further explored the role of neoadjuvant BEV plus DCC in patients with LAGC and discovered that BEV plus DCC as neoadjuvant therapy presented a good clinical response, with an ORR of 55.0% and a pathological response grade 2 in 40.0% of patients and grade 3 in 15.0% patients, which was numerically better than DCC chemotherapy alone as neoadjuvant therapy ( 25 ). The explanations might be that (1) BEV could inhibit the neovascularization and induce the regression of tumor blood vessels ( 16 ), meanwhile, chemotherapy exhibited the ability of anti-cancer cytotoxicity ( 27 ), therefore, BEV plus DCC might present a better anti-tumor effect; (2) BEV might enhance the chemosensitivity of gastric cancer cells via suppressing the VEGF- phosphatidylinositol 3 kinase/protein kinase B-survivin signaling cascade ( 28 ); thus, it combined with DCC could induce favorable outcomes.…”
Section: Discussionmentioning
confidence: 91%
“…Neoadjuvant chemotherapy has been extensively applied in patients with LAGC ( 25 , 26 ). For instance, neoadjuvant DCC shows an R0 resection rate of 86.7% and R1 resection rate of 4.5% in patients with resectable gastric cancer ( 25 ); in patients with LAGC, neoadjuvant docetaxel, cisplatin, and S-1 realizes a partial response rate of 57% and an SD rate of 43%; meanwhile, it also facilitates a pathological response grade 1a in 17% patients, grade 1b in 30% patients, grade 2 in 37% patients and grade 3 in 17% patients ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects are rarely severe and mostly consist of flu-like symptoms [ 9 , 18 ]. Treatment with G-CSF is rarely used when the patient is being treated with capecitabine since it has been suggested that the combination may increase the myelotoxicity of capecitabine through the proliferative activity of the bone marrow [ 19 ].…”
Section: Introductionmentioning
confidence: 99%